THE MYANMAR CRISIS: INTERROGATING THE LIMITS OF ASEAN’S CONSTRUCTIVE ENGAGEMENT AND NEW PATHWAYS TO PEACE - Saravanamuttu, Johan (AEI Insights, 2025)
The paper is structured in three parts. First, it presents briefly the history of the concept of Constructive Engagement (CE) which emerged as a foil for the Association of Southeast Asian Nations (ASEAN)’s to address the Cambodian conflict. CE was premised on ASEAN’s diplomatic culture of norm-setting and norm socialization via the ASEAN Way. The paper posits that ASEAN, as a regional entity, embeds inter-state constitutive and prescriptive norms with an imperative to regularly seek new modalities of intramural conflict management. ASEAN’s plurality and diversity of membership predisposes it to medium and long-term processes of norm-setting as the means to address regime legitimacy and accountability within the constraints of the ASEAN Way. An obvious question arises as to whether the Myanmar crisis presents itself as the extreme or limiting case to date of the efficacy of ASEAN’s CE approach as a subset of its diplomatic culture to manage recalcitrant states. ASEAN’s current engagement via its Five-Point Consensus approach to deal with the Myanmar crisis has yielded few positive outcomes four years after the military coup of 2021. The paper examines Malaysia’s active engagement with Myanmar under the CE rubric dating to Myanmar’s membership of ASEAN in 1997, which it advocated. In more recent years, Malaysia has also borne the brunt of the massive impact of Rohingya migration to its shores as a fallout of the Myanmar crisis. This predisposes Malaysia to play an important role, especially in 2025 as Chair of ASEAN. Finally, the paper explores a constructivist pathway out of the Myanmar impasse for ASEAN. It argues that innovative processes beyond ASEAN’s Five-Point Consensus approach to the Myanmar crisis are needed to return Myanmar to a situation of sovereign accountability. Beyond state-to-state engagements, non-state actors could also play a significant role regionally on respective national terrains. In its current situation of civil war, this calls for ASEAN to recognise and engage with all the key stakeholders of the Myanmar Resistance.